The Impact of Reading Habits on English Proficiency in South African Grade 4 Township Learners - Siyasanga Stella Bavuma; Lundi Nomlala (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The primary aim of this study is to study the influence of reading habits on English language proficiency among Grade 4 English First Additional Language learners in the O.R. Tambo Inland District. Employing a qualitative method guided by an interpretivist paradigm, this research gathered data through semi-structured interviews and focus group discussions. Thirty Grade Four learners and two teachers from selected township primary schools participated in the study. The collected data were subjected to a thematic analysis. The study highlighted key themes, including reading practices, challenges, and support structures, thereby revealing how these factors collectively influence the development of English language proficiency among Grade 4 FAL learners. The study's findings outline the main themes that emerged from the data, emphasizing how reading habits affect English language proficiency. This study concludes that consistent and well-supported reading plays an important role in shaping the English language proficiency of grade 4 EFAL learners. It contributes to the existing literature by providing context-specific insights into South African township schools, an area that has received little research. The study suggests implementing focused reading programs, enhancing access to reading materials at home and in schools, and providing teacher-led reading support.